2021
DOI: 10.1002/saj2.20312
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effect of tillage and straw retention in conservation agriculture systems on soil carbon storage

Abstract: The main principles of conservationagriculture (CA) are minimal soil disturbance, permanent soil cover, diversification of crop rotations, and retention of crop residues. Tillage has been implicated with increased soil organic C (SOC) mineralization, but recently this has been contested. Residue retention and cover crops result in higher soil C inputs and are therefore expected to increase SOC. This study aimed to evaluate the effect of 17 yr of residue retention (with and without) and tillage (plowing and no-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…High bulk densities cause root impedance and lead to poor crop emergence. There is no consensus regarding the effect of CA on soil bulk density, as some studies reported a higher soil bulk density with CA compared to CT [91,92], while others have not found significant differences [86,93] or reported lower soil bulk density in CA in comparison to CT [88,94]. These differences in bulk density in the different trials may be due in part to the typology of the farm.…”
Section: Bulk Densitymentioning
confidence: 99%
“…High bulk densities cause root impedance and lead to poor crop emergence. There is no consensus regarding the effect of CA on soil bulk density, as some studies reported a higher soil bulk density with CA compared to CT [91,92], while others have not found significant differences [86,93] or reported lower soil bulk density in CA in comparison to CT [88,94]. These differences in bulk density in the different trials may be due in part to the typology of the farm.…”
Section: Bulk Densitymentioning
confidence: 99%
“…Denitrification appeared to be the primary pathway for N loss under continuous corn, whereas nitrifier-denitrification controlled N loss under rotation corn. • Straw retention increased soil C by 0.47 mg C kg −1 in a site with higher initial C but had no effect on a low C site in a 17yr tillage study in Denmark (Gómez-Muñoz et al, 2021). Straw retention did, however, decrease soil bulk density at both sites.…”
mentioning
confidence: 84%
“…Intact soil core samples corresponding to two tillage treatments and two plant cover treatments were extracted from the CENTS long-term crop rotation and tillage experiment at Aarhus University's department of Agroecology in Flakkebjerg (55 Hansen et al, 2015). The soil was classified as a Glossic Phaeozem (Krogh and Greve, 1999) with a sandy loam texture consisting of 14.7 % clay (<2 µm), 13.7 % silt (2-20 µm), 42.6 % fine sand (20-200 µm) and 27 % coarse sand (200-2000 µm), and an average organic C content of 9.8 mg C g − 1 (Gómez-Muñoz et al, 2021). The average bulk density in the top 100 mm was 1.30 Mg m − 3 in CT and 1.42 g Mg m − 3 in NT.…”
Section: Study Site and Samplingmentioning
confidence: 99%